1996
DOI: 10.1111/j.1651-2227.1996.tb18217.x
|View full text |Cite
|
Sign up to set email alerts
|

N‐nitrosodimethylamine, nitrate and nitrate‐reducing microorganisms in human milk

Abstract: Of 54 milk samples from 54 healthy nursing women analysed for volatile N‐nitrosamines, 42 appeared negative. Trace amounts (below the detection limit 0.5 μgl−1) of N‐nitrosodimethylamine were detected in the milk of 10 mothers and two samples contained this compound at 1.1 and 1.2 μgl−1 respectively. Almost all samples investigated contained nitrate (mean 2.9 ± 2.3 mgl−1) and nitrate reducing microorganisms (mean 4.2 ± 1.0 log ml−1). The recent finding of N‐nitrosodimethylamine in human milk gives evidence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The level of NDMA in breast milk is assigned the average of estimates from Lakritz and Pensabeneand Uibu et al . No data were found reporting concentration of NDMA in infant formula specifically.…”
Section: Methodsmentioning
confidence: 99%
“…The level of NDMA in breast milk is assigned the average of estimates from Lakritz and Pensabeneand Uibu et al . No data were found reporting concentration of NDMA in infant formula specifically.…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, Sen et al ( 1984 ) verified the presence of NDMA, NDEA, NDBA, NPIP and NMOR in human milk, as the result of migration from rubber products, also at high levels, corresponding to 2,796 μg/kg (NDBA). Another study reported of 54 milk samples collected from healthy nursing Estonian women analysed for volatile N‐ NAs that two samples contained NDMA at 1.1 and 1.2 μg/L, respectively (Uibu et al, 1996 ).…”
Section: Introductionmentioning
confidence: 99%